Solid-state batteries and battery packs

By adopting alternately stacked positive electrode sheets and negative electrode sheet structures in solid-state batteries, and setting up a binder slurry layer around the negative electrode sheet, the short circuit risk caused by lithium dendrites is solved, and the stability and energy density of the battery are improved.

CN119181766BActive Publication Date: 2025-03-28ENPOWER (PEKING) INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411696938.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-28
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

When solid-state batteries use lithium metal as negative electrodes, the growth problems of lithium dendrites are serious, resulting in short circuit risk and affecting the stability and commercialization of the battery.

Method used

An alternately stacked positive electrode sheet and negative electrode sheet structure is adopted, wherein the positive projection of the negative electrode sheet is located in the positive electrode sheet, the size of the negative electrode sheet is smaller than that of the positive electrode sheet, and a binder slurry layer is arranged around it to make up for the size difference.

Benefits of technology

It effectively improves the structural stability and safety of the battery, enhances physical insulation performance, reduces the risk of short circuit, inhibits the growth of lithium dendrites, extends the battery life, and increases energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181766B_ABST
    Figure CN119181766B_ABST
Patent Text Reader

Abstract

The present invention provides a solid-state battery and a battery pack, and specifically relates to the technical field of secondary batteries. The solid-state battery includes a battery housing and a battery cell arranged inside the battery housing; the battery cell includes alternately stacked positive and negative pole pieces, the positive projection of the negative pole piece is located inside the positive pole piece, and the size of the negative pole piece is smaller than the size of the positive pole piece; a binder slurry layer is arranged around the negative pole piece to make up the size difference between the positive pole piece and the negative pole piece. In the solid-state battery provided by the present invention, the size of the negative pole piece is smaller than that of the positive pole piece, and a binder slurry layer is arranged around the negative pole piece to make up the size difference, which effectively improves the structural stability and safety of the battery, enhances the physical insulation performance of the battery cell, and prevents the risk of short circuit. At the same time, the binder slurry layer helps to inhibit the growth of lithium dendrites, enhance mechanical strength, improve thermal management, and extend battery life, thereby achieving an increase in battery energy density and comprehensive optimization of performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a solid-state battery and a battery pack. Background Art

[0002] With the rapid development of new energy technologies, solid-state batteries have attracted widespread attention due to their potential high safety and energy density. Nevertheless, solid-state batteries still face some challenges in practical applications, especially the risk of short circuit. Especially in solid-state batteries using lithium metal as the negative electrode, the growth problem of lithium dendrites is particularly serious, which not only affects the stability of the battery, but also limits its commercialization process. Therefore, researchers and industry practitioners have invested a lot of work in the anti-short circuit technology of solid-state batteries, especially in the design of pole piece structure.

[0003] In the traditional lithium battery preparation process, the "negative electrode wrapped in positive electrode" structural design is usually adopted, that is, the area of ​​the negative electrode sheet is larger than the area of ​​the positive electrode sheet. However, for solid-state batteries, due to the difference in size between the electrolyte layer and the positive and negative electrode layers, during the high-pressure pressing process, the mismatch of the electrode sheet size can easily cause the edge of the positive electrode sheet to produce shear force on the electrolyte layer. This shear force may cause the edge of the positive electrode sheet to pierce the electrolyte layer, and then contact the negative electrode layer, causing a short circuit in the battery. In addition, if lithium metal is used as the negative electrode material, the growth of lithium dendrites in different directions may also cause it to pierce the electrolyte layer or grow from the edge to contact the positive electrode, also causing a short circuit.

[0004] In order to solve this problem, insulating rings are used in the prior art to prevent short circuits between the positive and negative electrodes, such as using PP / PA materials. However, although the introduction of these insulating rings isolates the positive and negative electrodes to a certain extent, it also brings about the problems of reduced energy density and reduced pressure bearing capacity. In order to increase the energy density of the battery cell, there are attempts in the prior art to replace the material of the anti-short circuit ring with a sulfide solid electrolyte. Although this material has a certain ionic conductivity, due to the gap between the insulating ring and the positive electrode sheet, the problem of lithium dendrites piercing the short circuit still exists. Especially under high load conditions, the traditional negative electrode package positive electrode structure still faces the risk of short circuit. In addition, if a non-isostatic pressing or confined flat pressing method, such as roller pressing, is used, the pole piece is prone to deformation, making the insulating ring difficult to implement in terms of process.

[0005] There is an urgent need to develop a new short-circuit prevention method to address the challenges encountered by all-solid-state batteries in practical applications. This method should not only provide physical insulation, but also inhibit the formation of lithium dendrites to a certain extent, thereby significantly reducing the risk of battery short circuit. This will help improve the safety and reliability of all-solid-state batteries and promote their widespread application in the field of new energy.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] One of the objects of the present invention is to provide a solid-state battery, aiming to solve at least one of the above-mentioned technical problems in the prior art.

[0008] A second object of the present invention is to provide a battery pack.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] A first aspect of the present invention provides a solid-state battery comprising a battery housing and a battery cell disposed inside the battery housing;

[0011] The battery cell comprises alternately stacked positive electrode sheets and negative electrode sheets, the positive projection of the negative electrode sheet is located inside the positive electrode sheet, and the size of the negative electrode sheet is smaller than the size of the positive electrode sheet;

[0012] An adhesive slurry layer is arranged around the negative electrode sheet to make up for the size difference between the positive electrode sheet and the negative electrode sheet.

[0013] Furthermore, the binder slurry layer is formed by coating the binder slurry.

[0014] The binder slurry comprises, by weight, 0.1 to 10 parts of a binder, 30 to 80 parts of a filler and 10 to 70 parts of a solvent.

[0015] Furthermore, a positive electrode active material layer and a solid electrolyte layer are sequentially stacked on the positive electrode plate.

[0016] The solid electrolyte layer is formed by coating a solid electrolyte slurry.

[0017] The positive electrode active material layer includes, by mass, 30 to 95 parts of positive electrode active material, 4 to 60 parts of solid electrolyte, 0.5 to 5 parts of conductive agent and 0.5 to 5 parts of binder.

[0018] The solid electrolyte slurry comprises, by weight, 30 to 80 parts of a solid electrolyte, 0.1 to 10 parts of a binder, and 33 to 400 parts of a solvent.

[0019] Further, the binder includes at least one of polytetrafluoroethylene, polytetrafluoroethylene, styrene-butadiene rubber, nitrile rubber, polyurethane rubber and acrylate rubber;

[0020] The solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte and a composite electrolyte;

[0021] The solvent includes at least one of toluene, xylene, isobutyl isobutyrate, ethyl acetate, hexyl acetate, butyl butyrate, benzyl butyrate, ethylene dichloride and heptane.

[0022] Furthermore, the filler is a lithium-philic material.

[0023] The lithium-philic material includes at least one of a lithium compound, a carbon layer, and a metal oxide.

[0024] The lithium compound includes at least one of lithium oxide, lithium sulfide, lithium phosphide, lithium nitride and lithium salt.

[0025] The lithium salt includes lithium phosphate.

[0026] The carbon layer includes at least one of artificial graphite, hard carbon and soft carbon.

[0027] The metal oxide includes zinc oxide.

[0028] Furthermore, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, spinel lithium manganese oxide, lithium-rich manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel manganese cobalt oxide.

[0029] Furthermore, the positive electrode plate and the negative electrode plate are rectangular.

[0030] The length of the positive electrode plate is La, and the width is Wa, and the length of the negative electrode plate is Lb, and the width is Wb.

[0031] 0.4mm≤La-Lb≤4.5mm, 0.4mm≤Wa-Wb≤4.5mm.

[0032] Furthermore, the center of the negative electrode plate coincides with the center of the positive electrode plate, and La-Lb=Wa-Wb.

[0033] Furthermore, the double-sided surface loading of the solid-state battery is less than 38 mg / cm 2 , 0.4mm≤La-Lb<1.5mm, 0.4mm≤Wa-Wb<1.5mm.

[0034] Furthermore, 38 mg / cm 2 ≤ Double-sided surface loading of the solid-state battery <50mg / cm 2 , 1.5mm≤La-Lb<2.4mm, 1.5mm≤Wa-Wb<2.4mm.

[0035] Furthermore, 50 mg / cm 2 ≤ Double-sided surface loading of the solid-state battery < 60 mg / cm 2 , 2.4mm≤La-Lb<3.5mm, 2.4mm≤Wa-Wb<3.5mm.

[0036] Furthermore, the double-sided surface loading of the solid-state battery is ≥60 mg / cm 2 , 3.5mm≤La-Lb≤4.5mm, 3.5≤Wa-Wb≤4.5mm.

[0037] A second aspect of the present invention provides a battery pack, comprising a plurality of the solid-state batteries described above;

[0038] The solid-state batteries in the battery pack are connected in parallel.

[0039] Compared with the prior art, the present invention has at least the following beneficial effects:

[0040] The solid-state battery provided by the present invention comprises a battery cell comprising alternately stacked positive and negative electrode sheets, wherein the negative electrode sheet is smaller than the positive electrode sheet, and its positive projection is located inside the positive electrode sheet, and a binder slurry layer is arranged around it to make up for the size difference, which effectively improves the structural stability and safety of the battery. This design not only enhances the physical insulation performance of the battery cell, but also prevents the risk of short circuit. At the same time, the binder slurry layer helps to inhibit the growth of lithium dendrites, enhance mechanical strength, improve thermal management, and extend battery life, thereby achieving an increase in battery energy density and comprehensive optimization of performance, providing a new direction for the advancement of solid-state battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 A schematic diagram of the dimensions of a solid-state battery provided by the present invention;

[0043] Figure 2 is a charge / discharge voltage curve diagram of the solid-state battery of Example 1;

[0044] Figure 3 is a charge / discharge voltage curve diagram of the solid-state battery of Example 2;

[0045] Figure 4 is a charge / discharge voltage curve diagram of the solid-state battery of Comparative Example 1;

[0046] Figure 5 This is a photo of the negative electrode sheet after disassembly of Comparative Example 1. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0048] Hereinafter, the terms "including", "having" and their cognates, which may be used in various embodiments of the present invention, are intended only to indicate specific features, numbers, steps, operations, elements, components or combinations of the foregoing items, and should not be understood as first excluding the existence of one or more other features, numbers, steps, operations, elements, components or combinations of the foregoing items or adding the possibility of one or more features, numbers, steps, operations, elements, components or combinations of the foregoing items.

[0049] A first aspect of the present invention provides a solid-state battery comprising a battery housing and a battery cell disposed inside the battery housing;

[0050] The battery cell comprises alternately stacked positive electrode sheets and negative electrode sheets, the positive projection of the negative electrode sheet is located inside the positive electrode sheet, and the size of the negative electrode sheet is smaller than the size of the positive electrode sheet;

[0051] An adhesive slurry layer is arranged around the negative electrode sheet to make up for the size difference between the positive electrode sheet and the negative electrode sheet.

[0052] The solid-state battery provided by the present invention comprises a battery cell comprising alternately stacked positive and negative electrode sheets, wherein the negative electrode sheet is smaller than the positive electrode sheet, and its positive projection is located inside the positive electrode sheet, and a binder slurry layer is arranged around it to make up for the size difference, which effectively improves the structural stability and safety of the battery. This design not only enhances the physical insulation performance of the battery cell, but also prevents the risk of short circuit. At the same time, the binder slurry layer helps to inhibit the growth of lithium dendrites, enhance mechanical strength, improve thermal management, and extend battery life, thereby achieving an increase in battery energy density and comprehensive optimization of performance, providing a new direction for the advancement of solid-state battery technology.

[0053] Specifically, the present invention adopts the method of "positive electrode wrapped in negative electrode" to make the area of ​​the positive electrode plate larger than that of the negative electrode plate, which helps to improve the energy density of the battery. The solid electrolyte on the positive electrode plate combines the diaphragm function of the electrolyte into one, greatly reducing the distance between the positive and negative electrodes, reducing the thickness of the battery, and thus improving the volume energy density of the battery cell. The increase in the area of ​​the positive electrode plate can increase the active area of ​​the electrochemical reaction, which helps to improve the charging and discharging efficiency and performance of the battery. The increase in the area of ​​the positive electrode plate is conducive to maintaining an effective interfacial charge transfer channel and obtaining a cycle stability that is far superior to that of a liquid lithium battery. In an all-solid-state battery, the increase in the area of ​​the positive electrode plate helps to alleviate the degradation of the material structure caused by the electrochemical-mechanical effect during the battery cycle and maintain good electrochemical performance. The increase in the area of ​​the positive electrode plate helps to reduce the use of negative electrode materials, thereby reducing the risk of lithium dendrite growth and improving the safety of the battery.

[0054] The present invention achieves the consistency of the size of the electrolyte layer and the positive electrode sheet by adopting the method of positive electrode wrapped negative electrode. This design effectively avoids direct contact between the positive and negative electrode sheets, thereby significantly reducing the risk of short circuit. In addition, the binder slurry layer not only compensates for the size difference between the positive electrode sheet and the negative electrode sheet, but also prevents the edge stress generated by the size mismatch during the pressure application of the battery cell, which may cause the material to fall off, the so-called material drop phenomenon. This fine structural design helps to maintain the integrity and stability of the battery cell.

[0055] The use of the binder slurry layer plays multiple roles in improving battery performance. On the one hand, as a filler material, it can reduce stress concentration caused by size differences, thereby reducing the risk of damage to the battery cell during manufacturing and use. On the other hand, the addition of the binder slurry layer can also inhibit the growth of lithium dendrites to a certain extent, which is crucial to improving the safety of the battery and extending its service life.

[0056] In addition, the edge coating of the binder slurry not only solves the edge burr problem caused by cutting and improves the neatness of the battery appearance, but also effectively inhibits the lateral growth of lithium dendrites by inducing lithium deposition, further reducing the possibility of lithium dendrites contacting the positive electrode. This edge coating technology helps achieve more uniform current distribution and more stable battery performance by optimizing the deposition behavior of lithium ions.

[0057] Furthermore, the binder slurry layer is formed by coating the binder slurry.

[0058] The binder slurry comprises, by weight, 0.1 to 10 parts of a binder, 30 to 80 parts of a filler and 10 to 70 parts of a solvent.

[0059] Typically but not limiting, in the binder slurry, the binder may be 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, or any value within the range of 0.1 to 10 parts; the filler may be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts or 80 parts, or any value within the range of 30 to 80 parts; the solvent may be 10 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts or 70 parts, or any value within the range of 10 to 70 parts.

[0060] In a specific embodiment, the preparation process of the binder slurry layer is as follows: a polytetrafluoroethylene plate with the same size as the negative electrode is placed on the positive electrode plate, and then the slurry is introduced into a spray storage tank, and the slurry is sprayed around the positive electrode plate, and the spraying thickness is consistent with the thickness of the negative electrode.

[0061] In addition, the above-mentioned adhesive slurry can also be used for lug side coating, four-plane edge coating and eight-side coating.

[0062] The tab side coating refers to the coating of the adhesive slurry at the bottom of the area where the welding tab is left on the battery pole piece. The tab is the ear-shaped extension of the battery pole piece used to connect the internal and external circuits of the battery. Coating the adhesive slurry on the tab side can effectively prevent the short circuit caused by the contact between the positive and negative electrodes during the pole piece lamination process due to the exposure of the current collector.

[0063] Four-plane edge coating is the coating of adhesive slurry on the four planar edges of the battery pole piece. These edges are where the pole piece contacts or is stacked with other pole pieces. Four-plane edge coating helps reduce the risk of short circuits when the pole pieces are stacked and enhances the overall structure of the pole piece.

[0064] Eight-sided coating refers to the coating of adhesive slurry on the four planar edges and four side edges of the battery pole piece. This coating method provides comprehensive edge protection, which can minimize the risk of short circuits while enhancing the structural integrity of the pole piece and the mechanical stability of the battery.

[0065] Furthermore, a positive electrode active material layer and a solid electrolyte layer are sequentially stacked on the positive electrode plate.

[0066] The solid electrolyte layer is formed by coating a solid electrolyte slurry.

[0067] The positive electrode active material layer includes, by mass, 30 to 95 parts of positive electrode active material, 4 to 60 parts of solid electrolyte, 0.5 to 5 parts of conductive agent and 0.5 to 5 parts of binder.

[0068] Typically but not limiting, in the positive electrode active slurry, the positive electrode active material can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts or 95 parts, or any value within the range of 30 to 95 parts; the solid electrolyte can be 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts 6 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts or 60 parts, or any value in the range of 4 to 60 parts; the conductive agent can be 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 5 parts, or any value in the range of 0.5 to 5 parts; the binder can be 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 5 parts, or any value in the range of 0.5 to 5 parts.

[0069] It should be noted that the positive electrode active material layer can be prepared by a dry method or a wet method. When the positive electrode active material layer is prepared by a dry method, no solvent is included; when the positive electrode active material layer is prepared by a wet method, a solvent is included.

[0070] Specifically, the process of preparing the positive electrode active material layer by dry method includes: firstly, fully mixing the positive electrode active material, solid electrolyte and conductive agent, mixing at a speed of 300-15000 rpm for 0.5-5 hours, then adding a binder that can be fiberized, and fiberizing the binder by high-speed shear force to obtain a fluffy flocculent mixture; then, the fluffy flocculent mixture is subjected to high-temperature rolling to form a film to prepare the positive electrode active material layer. The temperature range of the high-temperature rolling process is 40-150°C, and the rolling speed is 1-15 m / min to obtain a positive electrode active material layer of target thickness.

[0071] The process of wet-process preparation of positive electrode active material layer includes: mixing the raw materials uniformly, coating them on the surface of current collector, the coating thickness is determined according to the surface density of positive electrode sheet, and then drying at 60-150°C for 0.5-6 hours to obtain positive electrode active material layer.

[0072] The solid electrolyte slurry comprises, by weight, 30 to 80 parts of a solid electrolyte, 0.1 to 10 parts of a binder, and 33 to 400 parts of a solvent.

[0073] Typically but not limiting, in the solid electrolyte slurry, the solid electrolyte may be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts or 80 parts, or any value within the range of 30 to 80 parts; the binder may be 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, or any value within the range of 0.1 to 10 parts; the solvent may be 40 parts, 50 parts, 60 parts, 65 parts, 100 parts, 200 parts, 300 parts or 400 parts, or any value within the range of 33 to 400 parts.

[0074] The solid electrolyte slurry is scraped on the surface of the positive electrode active material layer with a thickness of 30-500 μm. The coated positive electrode sheet is placed in a vacuum oven for drying at a temperature of 40-100°C for 1-24 hours.

[0075] Further, the binder includes at least one of polytetrafluoroethylene, polytetrafluoroethylene, styrene-butadiene rubber, nitrile rubber, polyurethane rubber and acrylate rubber;

[0076] The solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte and a composite electrolyte;

[0077] The solvent includes at least one of toluene, xylene, isobutyl isobutyrate, ethyl acetate, hexyl acetate, butyl butyrate, benzyl butyrate, ethylene dichloride and heptane.

[0078] During the battery manufacturing process, in order to ensure the compatibility of internal battery materials and the stability of battery performance, it is recommended to use the same binder, the same solid electrolyte and the same solvent when preparing binder slurry, solid electrolyte slurry and positive electrode active slurry.

[0079] Furthermore, the filler is a lithium-philic material, and the use of lithium-philic materials as fillers can significantly improve the performance of lithium metal batteries. This material effectively improves the electrochemical performance of the battery by enhancing the affinity of lithium ions, controlling the uniform deposition of lithium, inhibiting the growth of lithium dendrites, reducing nucleation overpotential and polarization potential, improving Coulomb efficiency and cycle life, and inducing uniform distribution of lithium metal nuclei. In addition, lithium-philic materials can also change the deposition direction of lithium metal, preventing lithium dendrites from piercing the electrolyte layer to cause soft short circuits, thereby enhancing the stability and cycle performance of the battery.

[0080] The lithium-philic material includes at least one of a lithium compound, a carbon layer, and a metal oxide.

[0081] The lithium compound includes at least one of lithium oxide, lithium sulfide, lithium phosphide, lithium nitride and lithium salt.

[0082] The lithium salt includes lithium phosphate.

[0083] The carbon layer includes at least one of artificial graphite, hard carbon and soft carbon.

[0084] The metal oxide includes zinc oxide.

[0085] Furthermore, the positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, spinel lithium manganese oxide, lithium-rich manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel manganese cobalt oxide.

[0086] Furthermore, the positive electrode plate and the negative electrode plate are rectangular.

[0087] The length of the positive electrode plate is La, and the width is Wa, and the length of the negative electrode plate is Lb, and the width is Wb.

[0088] 0.4mm≤La-Lb≤4.5mm, 0.4mm≤Wa-Wb≤4.5mm.

[0089] In the specific implementation process, the difference in length of the positive and negative electrode sheets can be 0.4mm, 1.0mm, 1.5mm, 2.0mm, 2.5mm, 3.0mm, 3.5mm, 4.0mm or 4.5mm, or any value in the range of 0.5mm~4.5mm; the difference in width of the positive and negative electrode sheets can be 0.4mm, 1.0mm, 1.5mm, 2.0mm, 2.5mm, 3.0mm, 3.5mm, 4.0mm or 4.5mm, or any value in the range of 0.4mm~4.5mm.

[0090] It should be noted that the difference between the length and width of the positive and negative electrode sheets can be the same or different.

[0091] Furthermore, the center of the negative electrode plate coincides with the center of the positive electrode plate, and La-Lb=Wa-Wb.

[0092] Furthermore, the double-sided surface loading of the solid-state battery is less than 38 mg / cm 2 , 0.4mm≤La-Lb<1.5mm, 0.4mm≤Wa-Wb<1.5mm.

[0093] In the specific implementation process, the difference in length or width of the positive and negative electrode sheets is independently 0.4mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1.0mm, 1.1mm, 1.2mm, 1.3mm or 1.4mm; it can also be any value in the range of 0.4mm~1.5mm (excluding 1.5mm).

[0094] Furthermore, 38 mg / cm 2 ≤ Double-sided surface loading of the solid-state battery <50mg / cm 2 , 1.5mm≤La-Lb<2.4mm, 1.5mm≤Wa-Wb<2.4mm.

[0095] In a specific implementation process, the difference in length or width of the positive and negative electrode sheets is independently 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2.0mm, 2.1mm, 2.2mm, 2.3mm or 2.4mm; it can also be any value within the range of 1.5mm~2.4mm (excluding 2.4mm).

[0096] Furthermore, 50 mg / cm 2 ≤ Double-sided surface loading of the solid-state battery < 60 mg / cm 2 , 2.4mm≤La-Lb<3.5mm, 2.4mm≤Wa-Wb<3.5mm.

[0097] In the specific implementation process, the difference in length or width of the positive and negative electrode sheets is independently 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.9mm, 3.0mm, 3.1mm, 3.2mm, 3.3mm or 3.4mm; it can also be any value in the range of 2.4mm~3.5mm (excluding 3.5mm).

[0098] Furthermore, the double-sided surface loading of the solid-state battery is ≥60 mg / cm 2 , 3.5mm≤La-Lb≤4.5mm, 3.5≤Wa-Wb≤4.5mm.

[0099] In the specific implementation process, the difference in length or width of the positive and negative electrode sheets is independently 3.5mm, 3.6mm, 3.7mm, 3.8mm, 3.9mm, 4.0mm, 4.1mm, 4.2mm, 4.3mm or 4.4mm; it can also be any value in the range of 3.5mm~4.5mm (excluding 4.5mm).

[0100] In one embodiment of the present invention, a solid-state battery includes a positive electrode sheet, a negative electrode sheet and a binder slurry layer. Figure 1 a in the figure is the positive electrode sheet, with a size of 60mm×90mm; Figure 1 b in the figure is the negative electrode, with a size of 58mm×88mm; Figure 1The c in the figure is a binder slurry layer, which is arranged around the negative electrode sheet to make up for the size difference between the positive electrode sheet and the negative electrode sheet. Therefore, the area of ​​the negative electrode sheet and the binder slurry layer is the same as that of the positive electrode sheet.

[0101] A second aspect of the present invention provides a battery pack, comprising a plurality of the solid-state batteries described above;

[0102] The solid-state batteries in the battery pack are connected in parallel.

[0103] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0104] Example 1

[0105] This embodiment provides a solid-state battery, and the preparation process is as follows:

[0106] 1. Mix 80g of lithium cobalt nickel manganese oxide (NCM811), 18g of lithium phosphorus sulfur chloride (LPSCL), and 2g of conductive agent VGCF at a mass ratio of 300 rpm for 2 hours. Add 3g of polytetrafluoroethylene (PTFE) to the resulting mixture, and fully fiberize it through high shear force at a speed of 12,000 rpm to obtain a fluffy flocculent mixture. The fluffy flocculent mixture is subjected to high-temperature roller pressing at a rolling temperature of 80°C and a speed of 7m / min to obtain a positive electrode layer with a thickness of 182μm and a positive electrode active material of 60.8 mg / cm 2 .

[0107] 2. Disperse solid electrolyte lithium phosphorus sulfur chloride (LPSCL) powder in 50g solvent toluene, the content of LPSCL is 50g, and then add 1g of binder NBR, stir for 2h, stirring speed 500rpm, to obtain solid electrolyte slurry. The solid electrolyte slurry is coated on the positive electrode layer, and after drying at 100℃ for 12h, a positive electrode sheet is obtained, wherein the thickness of the lithium phosphorus sulfur chloride (LPSCL) electrolyte layer is 100μm.

[0108] 3. Place the two positive electrode sheets with the sides not coated with the solid electrolyte layer facing each other, place the double-sided carbon-coated aluminum foil current collector between the two positive electrode sheets (the size of the positive electrode sheets is 60×90 mm), and press the two positive electrode sheets and the double-sided carbon-coated aluminum foil current collector together at a pressure of 30 MPa to obtain a composite positive electrode structure.

[0109] 4. Disperse LATP powder in solvent toluene so that the content of LATP in 100g toluene is 30g, and then add 1g of binder NBR, stir for 2h, and stir at a rate of 500rpm to obtain binder slurry. Place a PTFE sheet (the size of the sheet is 56×86mm) on one side of the solid electrolyte layer of the composite positive electrode, introduce the binder slurry into the spray tank, and use the spray equipment to spray the exposed part of the composite positive electrode plate. The final spray thickness is 50μm Figure 5 .

[0110] 5. Stack lithium metal as the negative electrode with the composite positive electrode structure, apply 0.5MPa pressure for pressing to obtain a solid-state battery cell, and put on the battery shell to obtain a solid-state battery.

[0111] Example 2

[0112] This embodiment provides a solid-state battery. The difference from Embodiment 1 is that zinc oxide is used to replace LATP therein. The remaining methods and steps are the same as those in Embodiment 1 and will not be repeated here.

[0113] Example 3

[0114] This embodiment provides a solid-state battery, and the preparation process is as follows:

[0115] 1. Same as the step in Example 2.

[0116] 2. Same as the step in Example 2.

[0117] 3. Same as the step in Example 2.

[0118] 4. The difference from Example 2 is that the content of zinc oxide is 80wt%, the content of binder is 10wt%, and the rest of the methods and steps are the same as the step in Example 2.

[0119] 5. Same as the step in Example 2.

[0120] Example 4

[0121] This embodiment provides a solid-state battery, and the preparation process is as follows:

[0122] 1. Same as the step in Example 2.

[0123] 2. Same as the step in Example 2.

[0124] 3. Same as the step in Example 2.

[0125] 4. The difference from Example 2 is that the content of zinc oxide is 50wt%, the content of binder is 5wt%, and the rest of the methods and steps are the same as the step in Example 2.

[0126] 5. Same as the step in Example 2.

[0127] Example 5

[0128] This embodiment provides a solid-state battery. The difference from Embodiment 2 is that the size of the thin plate is 56.5×86.5 mm. The remaining methods and steps are the same as those in Embodiment 2 and will not be repeated here.

[0129] Example 6

[0130] This embodiment provides a solid-state battery. The difference from Embodiment 2 is that the size of the thin plate is 55.5×85.5 mm. The remaining methods and steps are the same as those in Embodiment 2 and will not be repeated here.

[0131] Example 7

[0132] This embodiment provides a solid-state battery. The difference from Embodiment 2 is that the size of the thin plate is 58.5×88.5 mm. The remaining methods and steps are the same as those in Embodiment 2 and will not be repeated here.

[0133] Example 8

[0134] This embodiment provides a solid-state battery. Different from the embodiment 2, the positive electrode active material surface loading is 53.4 mg / cm 2 The size of the thin plate is 57×87 mm, and the remaining methods and steps are the same as those in Example 2 and will not be repeated here.

[0135] Example 9

[0136] This embodiment provides a solid-state battery. Different from the embodiment 1, the positive electrode active material surface loading is 41.6 mg / cm 2 The size of the thin plate is 58×88 mm, and the remaining methods and steps are the same as those in Example 1 and will not be repeated here.

[0137] Example 10

[0138] This embodiment provides a solid-state battery. Different from the embodiment 2, the positive electrode active material surface loading is 37.0 mg / cm 2 The size of the thin plate is 59×89 mm, and the remaining methods and steps are the same as those in Example 2 and will not be repeated here.

[0139] Comparative Example 1

[0140] This comparative example provides a solid-state battery. The difference from Example 2 is that step 4 is omitted, and the remaining steps are the same as those in Example 2 and will not be repeated here.

[0141] Comparative Example 2

[0142] This comparative example provides a solid-state battery. The difference from Example 2 is that step 4 is omitted, the size of the negative electrode plate is consistent with that of the positive electrode plate, both of which are 60×90 mm, and the remaining steps are the same as those in Example 2 and will not be repeated here.

[0143] Test Example 1

[0144] The all-solid-state batteries of Example 1 and Example 2 were charged and discharged at 60°C, 0.05°C, and 4MPa pressure. The charge / discharge voltage curves are shown in FIG. Figure 2 , Figure 3 As shown. Plotting the data in the process gives Figure 2 and Figure 3 .

[0145] from Figure 2 It can be seen that the solid-state battery provided in Example 1 can ensure that the all-solid-state battery can perform long cycles normally under high load by adjusting the negative electrode size and applying the LATP protective layer in the case of a relatively thin electrolyte thickness, laying the foundation for the industrialization of high energy density all-solid-state batteries.

[0146] from Figure 3 It can be seen that after the solid-state battery protection layer provided in Example 2 is replaced with zinc oxide, it can also play the role of preventing lithium dendrites, and zinc oxide has a lower cost and is a better choice in the industrialization process.

[0147] Test Example 2

[0148] The solid-state battery obtained in Comparative Example 1 was charged and discharged at 60°C, 0.05°C, and 4MPa pressure. The charge / discharge voltage curve is shown in FIG. Figure 4 shown.

[0149] from Figure 4 It can be seen that comparative example 1 has a 2 Under high surface load conditions, it is easy for lithium dendrites to cause a short circuit in the battery. Disassemble the battery and take photos. Figure 5 As shown, lithium dendrite growth occurs at the edge.

[0150] Test Example 3

[0151] The solid-state batteries of the embodiment and the comparative example were subjected to electrical performance tests, specifically, charge and discharge tests were performed at 0.05C. The results are shown in Table 1.

[0152] Table 1

[0153]

[0154] As can be seen from Table 1, a suitable negative electrode size can also avoid the short circuit caused by the growth of lithium dendrites in lithium metal negative electrode batteries. In addition, a protective layer is coated on the surface of the positive electrode plate coated with electrolyte. On the one hand, it can effectively ensure the insulation between the positive and negative electrodes between the plates, and on the other hand, it can effectively regulate lithium deposition to ensure stable battery circulation.

[0155] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A solid-state battery, characterized in that: It includes a battery housing and a battery cell arranged inside the battery housing; The battery cell comprises alternately stacked positive electrode sheets and negative electrode sheets, the positive projection of the negative electrode sheet is located inside the positive electrode sheet, and the size of the negative electrode sheet is smaller than the size of the positive electrode sheet; A binder slurry layer is provided around the negative electrode sheet to make up for the size difference between the positive electrode sheet and the negative electrode sheet; The binder slurry layer is formed by coating the binder slurry; The binder slurry comprises 0.1 to 10 parts of a binder, 30 to 80 parts of a filler and 10 to 70 parts of a solvent in parts by weight; The filler is a lithium-philic material; The lithium-philic material includes at least one of a lithium compound, a carbon layer, and a metal oxide; The lithium compound includes at least one of lithium oxide, lithium sulfide, lithium phosphide, lithium nitride and lithium salt; The lithium salt includes lithium phosphate; The carbon layer includes at least one of artificial graphite, hard carbon and soft carbon; The metal oxide includes zinc oxide.

2. The solid-state battery according to claim 1, characterized in that: The positive electrode sheet is provided with a positive electrode active material layer and a solid electrolyte layer stacked in sequence; The solid electrolyte layer is formed by coating a solid electrolyte slurry; the positive electrode active material layer includes 30-95 parts of positive electrode active material, 4-60 parts of solid electrolyte, 0.5-5 parts of conductive agent and 0.5-5 parts of binder by weight; The solid electrolyte slurry comprises, by weight, 30 to 80 parts of a solid electrolyte, 0.1 to 10 parts of a binder, and 33 to 400 parts of a solvent.

3. The solid-state battery according to claim 2, characterized in that: The binder comprises at least one of polytetrafluoroethylene, polytetrafluoroethylene, styrene-butadiene rubber, nitrile rubber, polyurethane rubber and acrylate rubber; The solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte and a composite electrolyte; The solvent includes at least one of toluene, xylene, isobutyl isobutyrate, ethyl acetate, hexyl acetate, butyl butyrate, benzyl butyrate, ethylene dichloride and heptane.

4. The solid-state battery according to claim 2, characterized in that: The positive electrode active material includes at least one of lithium cobalt oxide, lithium manganese oxide, spinel lithium manganese oxide, lithium-rich manganese oxide, lithium nickel cobalt aluminum oxide and lithium nickel manganese cobalt oxide.

5. The solid-state battery according to any one of claims 1 to 4, characterized in that: The positive electrode sheet and the negative electrode sheet are rectangular; The length of the positive electrode plate is La, and the width is Wa, and the length of the negative electrode plate is Lb, and the width is Wb; 0.4mm≤La-Lb≤4.5mm, 0.4mm≤Wa-Wb≤4.5mm.

6. The solid-state battery according to claim 5, characterized in that: The center of the negative electrode plate coincides with the center of the positive electrode plate, and La-Lb=Wa-Wb.

7. The solid-state battery according to claim 5, characterized in that: The double-sided surface loading of the solid-state battery is less than 38 mg / cm 2 , 0.4mm≤La-Lb<1.5mm, 0.4mm≤Wa-Wb<1.5mm; or, 38mg / cm 2 ≤ Double-sided surface loading of the solid-state battery <50mg / cm 2 , 1.5mm≤La-Lb<2.4mm, 1.5mm≤Wa-Wb<2.4mm; or, 50mg / cm 2 ≤ Double-sided surface loading of the solid-state battery < 60 mg / cm 2 , 2.4mm≤La-Lb<3.5mm, 2.4mm≤Wa-Wb<3.5mm; or, The double-sided surface loading of the solid-state battery is ≥60 mg / cm 2 , 3.5mm≤La-Lb≤4.5mm, 3.5mm≤Wa-Wb≤4.5mm.

8. A battery pack, characterized in that: A solid-state battery comprising a plurality of batteries according to any one of claims 1 to 7; The solid-state batteries in the battery pack are connected in parallel.

Citation Information

Patent Citations

  • Solid-state lithium ion battery and battery cell winding method thereof

    CN118173904A

  • Laminated cell, secondary battery and electric device

    CN220367979U